Hearing the physical condition: The relationship between sexually dimorphic vocal traits and underlying physiology - Chen, Shitao; Han, Chengyang; Wang, Shuai; Liu, Xuanwen; Wang, Bin; Wei, Ran; Lei, Xue (Frontiers in Psychology, 2022)
A growing amount of research has shown associations between sexually dimorphic vocal traits and physiological conditions related to reproductive advantage. This paper presented a review of the literature on the relationship between sexually dimorphic vocal traits and sex hormones, body size, and physique. Those physiological conditions are important in reproductive success and mate selection. Regarding sex hormones, there are associations between sex-specific hormones and sexually dimorphic vocal traits; about body size, formant frequencies are more reliable predictors of human body size than pitch/ fundamental frequency; with regard to the physique, there is a possible but still controversial association between human voice and strength and combat power, while pitch is more often used as a signal of aggressive intent in conflict. Future research should consider demographic, cross-cultural, cognitive interaction, and emotional motivation influences, in order to more accurately assess the relationship between voice and physiology. Moreover, neurological studies were recommended to gain a deeper understanding of the evolutionary origins and adaptive functions of voice modulation.